Increasing Productivity, Quality, Hygiene and Marketing of Tofu Processed Products in Gunungpati District, Semarang City - Danang Dwi Saputro; Astuti, Pudji; Santoso, Dwi Budi; Rachmadi, Moch Faizal (Unram Journal of Community Service, 2024)
Semarang City is one of the areas in Central Java Province that has various potential superior regional products, one of which is soybean processing in Sumurrejo Village, Gunungpati District. The abundant potential for soybean processing has made Sumurrejo Village designated as a Thematic Soybean Processing Village (OKE Village). There are a total of 16 soybean processing producers divided into 8 tofu producers and 8 tempeh producers, including Berkah Hambida and UD Jaya Makmur which focus on tofu processing. The problems faced by the two producers include the production aspect, namely the lack of standardized and adequate infrastructure, the absence of Appropriate Technology (TTG) and the lack of hygiene in the production area. In addition, problems in terms of quality, marketing and the environment are also still very minimal. There is no standardized Wastewater Treatment Plant (IPAL) and the market segment is still limited to the local and regional scope. The purpose of community service is to overcome problems in terms of production and marketing. More specifically, these problems include aspects of production, quality, hygiene and environmental aspects. The service methods used are through socialization, training, technology application, mentoring and evaluation as well as program sustainability. The results of the service in the 1st year (2024) were to create and implement 1 unit of steam boiler machine, 1 set of food grade stainless steel boiling pans and optimization of the Wastewater Treatment Plant (IPAL).